Computation and molecular pharmacology to trace the anti-rheumatoid activity of Angelicae Pubescentis Radix - Junhao Zhang; Rui Wang; Xiao Liang; Hao Tian Bai; Ya Lan Li; Shuhui Sun; Qianqian Zhang; Jing Yang (BMC, 2022)
Abstract Background The mechanism of action of Angelicae Pubescentis Radix in rheumatoid arthritis treatment is complex; the pathways and protein targets involved remain unclear. This study predicted the targets and signaling pathways of Angelicae Pubescentis Radix for rheumatoid arthritis treatment using network pharmacology and molecular docking technology and clarified its mechanism of action using in vitro cellular experiments. Methods Angelicae Pubescentis Radix active components and related targets were retrieved from the traditional Chinese medicine systems pharmacology database. All human proteins were mined from the global protein database, and the network of active components and targets of Angelicae Pubescentis Radix was drawn using Cytoscape 3.7.1. GeneCard, Online Mendelian Inheritance in Man, and DrugBank databases were used to mine rheumatoid arthritis-related genes. Metascape was used for Gene Ontology function analysis and Kyoto Encyclopedia of Genes and Genomes enrichment pathways. β-sitosterol's molecular docking was determined using AutoDock Tools; pathway verification was performed in the Kyoto Encyclopedia of Genes and Genomes database, and the verified genes were input into the Human Protein Atlas database to observe the expression levels in various human body tissues. Results Eight main active components were screened out of Angelicae Pubescentis Radix from the traditional Chinese medicine systems pharmacology database, and 60 targets related to major active ingredients were obtained. Forty-two core pathogenic rheumatoid arthritis-related genes were screened from GeneCard and other related databases. The enrichment of the Kyoto Encyclopedia of Genes and Genomes pathway included the vascular endothelial growth factor signaling pathway that proved to be the decisive pathway for rheumatoid arthritis treatment by a high degree value. In vitro experiments confirmed that Angelicae Pubescentis Radix mainly regulated cell proliferation and survival through the vascular endothelial growth factor signaling pathway and showed significant therapeutic effects on rheumatoid arthritis. The prostaglandin endoperoxide synthase 2 gene was associated with rheumatoid arthritis via pathway verification and monitoring of human gene expression levels. Conclusions The mechanism of the multi-component, multi-target, and multi-channel treatment of rheumatoid arthritis via Angelicae Pubescentis Radix was explored using network pharmacology and molecular docking technology, providing new thinking and research directions for future rheumatoid arthritis treatment using Angelicae Pubescentis Radix.